Impact of combination therapy with statin and ezetimibe on secondary prevention for post-acute myocardial infarction patients in the statin era. (1st September 2015) - Ebisawa, Soichiro; Izawa, Atsushi; Ueki, Yasushi; Hioki, Hirofumi; Minamisawa, Masatoshi; Hashizume, Naoto; Abe, Naoyuki; Kashima, Yuichiro; Miura, Takashi; Takeuchi, Takahiro; Motoki, Hirohiko; Okada, Ayako; et al.
Abstract: Background: Little is known concerning the effect of ezetimibe for secondary prevention in post-myocardial infarction (MI) patients. In this study, we investigated the secondary prevention effect of ezetimibe for post-MI patients. Methods: This study is a retrospective analysis of Assessing Lipophilic vs. hydrophilic Statin therapy for Acute MI (ALPS-AMI study). The patients were divided into two groups: those administered a statin to control low density lipoprotein-cholesterol (LDL-C), the ezetimibe(−) group, and those administered ezetimibe in addition to a statin to control LDL-C, the ezetimibe(+) group. The endpoints were Major Adverse Cardiac and Cerebrovascular Event (MACCE), including all-cause death, recurrence of MI, stroke, and heart failure requiring hospitalization, and MACCE with revascularization. Results: The ezetimibe(+) and ezetimibe(−) groups contained 113 and 337 patients, respectively. Incidences of MACCE and MACCE with revascularization were lower in the ezetimibe(+) group than in the ezetimibe(−) group (2.6% vs. 11.5%, p = 0.002; 23.0% vs. 36.7%, p = 0.014, respectively). Moreover, logistic regression analysis revealed ezetimibe(+) was a significant negative predictor of MACCE (OR 0.208, 95% CI 0.048 to 0.903, p = 0.047) and MACCE with revascularization (OR 0.463, 95% CI 0.258 to 0.831, p = 0.008). The preventive effect of ezetimibe against MACCE was observed in both moderate- and high-intensity lipid lowering treatment groups (0% vs. 17%; p = 0.077, 3.1% vs. 9.4%; p = 0.033). Conclusions: In lipid-lowering therapy post-MI, ezetimibe and statin combination therapy improved MACCE with or without revascularization compared with statin monotherapy. These findings suggest that post-MI secondary prevention should be more intensive.